Stable isotopes in ecosystem science: structure, function and dynamics of a subtropical savanna - Boutton, T. W.; Archer, S. R.; Midwood, A. J. (Rapid communications in mass spectrometry, 1999)
Stable isotopes are often utilized as intrinsic tracers to study the effects of human land uses on the structural and functional characteristics of ecosystems. Here, we illustrate how stable isotopes of H, C, and O have been utilized to document changes in ecosystem structure and function using a case study from a subtropical savanna ecosystem. Specifically, we demonstrate that: (1) δ13C values of soil organic carbon record a vegetation change in this ecosystem from C4 grassland to C3 woodland during the past 40–120 years, and (2) δ2H and δ18O of plant and soil water reveal changes in ecosystem hydrology that accompanied this grassland‐to‐woodland transition. In the Rio Grande Plains of North America, δ13C values of plants and soils indicate that areas now dominated by C3 subtropical thorn woodland were once C4 grasslands. δ13C values of current organic matter inputs from wooded landscape elements in this region are characteristic of C3 plants (−28 to −25‰), while those of the associated soil organic carbon are higher and range from −20 to −15‰. Approximately 50–90% of soil carbon beneath the present C3 woodlands is derived from C4 grasses. A strong memory of the C4 grasslands that once dominated this region is retained by δ13C values of organic carbon associated with fine and coarse clay fractions. When δ13C values are evaluated in conjunction with 14C measurements of that same soil carbon, it appears that grassland‐to‐woodland conversion occurred largely within the past 40–120 years, coincident with the intensification of livestock grazing and reductions in fire frequency. These conclusions substantiate those based on demographic characteristics of the dominant tree species, historical aerial photography, and accounts of early settlers and explorers. Concurrent changes in soil δ13C values and organic carbon content over the past 90 years also indicate that wooded landscape elements are behaving as sinks for atmospheric CO2 by sequestering carbon derived from both the previous C4 grassland and the present C3 woody vegetation. Present day woodlands have hydrologic characteristics fundamentally different from those of the original grasslands. Compared to plants in remnant grasslands, tree and shrub species in the woodlands are rooted more deeply and have significantly greater root biomass and density than grasslands. δ18O and δ2H values of plant and soil water confirm that grassland species acquire soil water primarily from the upper 0.5 m of the soil profile. In contrast, trees and shrubs utilize soil water from throughout the upper 4 m of the profile. Thus, soil water that formerly may have infiltrated beyond the reach of the grassland roots and contributed to local groundwater recharge or other hydrologic fluxes may now be captured and transpired by the recently formed woodland plant communities. The natural abundances of stable isotopes revealed fundamental information regarding the impacts of human land use activities on the structure and function of this subtropical savanna. Stable isotopes provided direct, spatially explicit evidence for dramatic changes in ecosystem physiognomy and demonstrated some functional consequences for the hydrologic cycle. Furthermore, grassland‐to‐woodland conversion has been geographically extensive in the worlds' drylands, suggesting that these ecosystem‐level changes in vegetation structure, carbon cycling, and hydrology may have implications for regional/global biogeochemistry and climate. Copyright © 1999 John Wiley &Sons, Ltd.